The Fundamentals of an Electronic-Based Federal Securities Act - James D. Cox (Washington University Law Quarterly, 1997)
This Article examines what the structure of an electronic-based securities act would be if technological conditions that prevail today existed as well in 1933.
Keywords: Electronic trading of securities